After the reflexive turn in migration studies: Towards the doing migration approach - Amelina, Anna (Population space and place, 2021)
What processes transform (im)mobile individuals into ‘migrants’ and geographic movements across political‐territorial borders into ‘migration’? Addressing this question, the article develops the doing migration approach that combines socio constructivist, praxeological and the sociology of knowledge and performativity perspectives. ‘Doing migration’ starts with the processes of social attribution that separate between ‘migrants’ and ‘nonmigrants’ and that are embedded into institutional, organisational and interactional routines which generate unique social order(s) of migration. Illustrating these conceptual ideas, the article provides insights into the elements of the contemporary European order of ‘migration’. The institutional routines contribute to the emergence of the European migration regime that includes narratives of economisation, securitisation and humanitarisation. The organisational routines of European migration order realise bordering, surveillance and othering contributing to the disciplining effects on those defined as ‘migrants’. Furthermore, the routines of daily face‐to‐face interactions generate various microforms of ‘migration’ by stigmatisation, while also giving the potential to resist the social attribution as ‘migrant’.